THE SIMULATION OF SKEG EFFECT TO BARGE RESISTANCE CALCULATION USING CFD-RANS OPENFOAM - Hasmi, Abrari Noor; Nurcholik, Samsu Dlukha (Badan Pengkajian dan Penerapan Teknologi, 2020)
The paper discusses the significance of different types of skegs in a barge toward the pressure, fluid velocity and the ship?s total resistance. There are three kinds of skeg configurations: barge without skegs, skegs without deflection, and skegs with deflection. The barge was towed with forward speed were ranging across 3 knots ? 9 knots. The simulations were conducted using an open-source RANS (Reynold Averaged Numerical Simulation) CFD code Open-FOAM. The simulations show that the skegs raise the barge?s resistance. The skegs with deflection have a bigger resistance amplification compared to skegs without deflection.